DRUG DOSE ADJUSTMENT IN CHRONIC KIDNEY FAILURE PATIENTS AT HOSPITAL X - Nurdiansyah, Iid; Susilo, Rinto; Setyaningsih, Indah; Putri, Anisa (Medical Sains : Jurnal Ilmiah Kefarmasian, 2025)
Chronic Kidney Disease (CKD) is a significant global health issue, with increasing incidence rates, high treatment costs, and poor prognosis. Adjusting drug dosages in patients with CKD is essential to prevent worsening conditions and ensure proper therapy. This study examines the drug adjustment practices at Hospital X. This research method uses a descriptive research uses secondary data from medical records (Jan-Dec 2021) of CKD patients at Hospital X. Data include patient demographics, comorbidities, medications, and dosage adjustments according to the Renal Pharmacotherapy Handbook. Results: Among the 52 patients, the majority were female (60%) and aged 46-65 years (57%). Ranitidine was the most prescribed drug (47.37%) for CKD patients, with 56.76% dosages aligning with renal dosing guidelines. This study concluded that ranitidine was the most common medication, and over half of the prescriptions were aligned with the renal dosing guidelines. Keywords: drug dose adjustment, chronic kidney failure,  renal pharmacotherapy